1997
DOI: 10.1016/s0924-9338(97)80015-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zolpidem in insomnia

Abstract: SummaryThe efficacy of zolpidem, a non benzodiazepine hypnotic agent with a short elimination half life, was reviewed, analysing more than 50 international clinical trials published since 1986. The hypnotic activity of zolpidem has been explored in different patient populations including normal volunteers, general practice outpatients and psychiatric out- or in-patients with varying sleep disorders; both transient and chronic. Assessment methods used have included objective and subjective measures of hypnotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Reviewing 12 short-term, 7 medium-term and 5 longterm studies regarding the subjective assessment of the hypnotic efficacy of zolpidem by means of questionnaires or clinical global assessment scales as well as 10 placebocontrolled studies on objective measures of hypnotic activity involving the use of polysomnography, Priest et al [55] concluded that the hypnotic efficacy of zolpidem had repeatedly been demonstrated in polysomnographic studies, with subjective assessments confirming these results. However, as these patients were generally referred to as chronic insomniacs, psychiatric inpatients, insomniac outpatients or elderly insomniacs, it remains open which specific sleep disorder -as for instance defined in the ICSD or DSM-IV -would benefit most from zolpidem.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing 12 short-term, 7 medium-term and 5 longterm studies regarding the subjective assessment of the hypnotic efficacy of zolpidem by means of questionnaires or clinical global assessment scales as well as 10 placebocontrolled studies on objective measures of hypnotic activity involving the use of polysomnography, Priest et al [55] concluded that the hypnotic efficacy of zolpidem had repeatedly been demonstrated in polysomnographic studies, with subjective assessments confirming these results. However, as these patients were generally referred to as chronic insomniacs, psychiatric inpatients, insomniac outpatients or elderly insomniacs, it remains open which specific sleep disorder -as for instance defined in the ICSD or DSM-IV -would benefit most from zolpidem.…”
Section: Discussionmentioning
confidence: 99%
“…The hypnotic activity of zolpidem has also been explored in different patient populations and assessment included both objective and subjective measures of hypnotic efficacy for different treatment durations, with results confirming that 10 mg is superior to placebo [32]. Consequently, 10 mg is the recommended dose for the short‐term treatment of insomnia in the nonelderly; in elderly patients 5 mg has been shown to be effective at inducing sleep while giving an optimum safety profile [33].…”
Section: Zolpidemmentioning
confidence: 99%
“…A large number of clinical studies of the efficacy of zolpidem in inducing and maintaining sleep, involving tens of thousands of patients, have been carried out and the results have been published. Several detailed reviews of this literature are available (44,59,95). Zolpidem's activity has been evaluated using subjective assessments in which patients responded to questionnaires concerning the latency, quality, and duration of their sleep.…”
Section: Clinical Experience With Zolpidem Efficacymentioning
confidence: 99%